Efficacy of cognitive behavioral therapy for stimulant use disorders: a systematic review and meta-analysis - Kim, Jongtae; Kwak, Jaeseok; Jeong, Hyunsuk; Kim, Na Jin; Lee, Seung-Yup; Kim, Yangsik; Kim, Jangrae; Han, Sooyeon; Chun, Hae-ryoung; Park, Kyoung Jae; Lee, Soo-Bi; Kim, Gyeongmin; et al. (Frontiers in Psychiatry, 2025)
BackgroundCognitive Behavioral Therapy (CBT) is a widely used psychosocial intervention for stimulant use disorder (SUD). However, its independent efficacy is not well established, as previous reviews often combine it with other interventions or compare it to comparators with active components. To clarify its specific contribution, this systematic review and meta-analysis aimed to determine the efficacy of standalone CBT compared to minimal-treatment controls for achieving abstinence in individuals with SUD.MethodsWe conducted a systematic search of PubMed, Embase, PsycINFO, and the Cochrane Library through May 15, 2025, for randomized controlled trials (RCTs) that compared standalone CBT with minimal-treatment comparators, such as treatment-as-usual or wait-list controls, for individuals with SUD. The primary outcome was short-term stimulant abstinence. We used the Cochrane Risk of Bias 2.0 tool for risk of bias assessment and pooled odds ratios (ORs) using a random-effects model. The review protocol was registered with PROSPERO (CRD420251012327).ResultsNine RCTs met the inclusion criteria, with eight trials (849 participants) included in the meta-analysis. Standalone CBT was associated with higher odds of achieving short-term (4–24 weeks) stimulant abstinence compared to minimal-treatment controls (OR = 2.88, 95% CI = 1.08–7.70), although between-study heterogeneity was substantial (I² = 75.62%). The certainty of this evidence was rated as low using the GRADE approach, due to risk of bias and imprecision. Treatment dropout rates were similar between CBT and control groups (OR = 1.13, 95% CI = 0.67–1.91), and no CBT-related adverse events were reported.ConclusionsThe findings suggest that standalone CBT may increase short-term abstinence from stimulants. However, given the low certainty of the evidence, the effect estimate should be interpreted cautiously, and more high-quality research is needed. This research was funded by the Ministry of Health and Welfare, Republic of Korea.Systematic Review RegistrationPROSPERO, identifier CRD420251012327.